Markers of Novelty Processing in Older Adults Are Stable and Reliable - Behforuzi, Hura; Feng, Nicole C.; Billig, Adam R.; Ryan, Eliza; Tusch, Erich S.; Holcomb, Phillip J.; Mohammed, Abdul H.; Daffner, Kirk R. (Frontiers in Aging Neuroscience, 2019)
Exploratory behavior and responsiveness to novelty play an important role in maintaining cognitive function in older adults. Inferences about age- or disease-related differences in neural and behavioral responses to novelty are most often based on results from single experimental testing sessions. There has been very limited research on whether such findings represent stable characteristics of populations studied, which is essential if investigators are to determine the result of interventions aimed at promoting exploratory behaviors or draw appropriate conclusions about differences in the processing of novelty across diverse clinical groups. The goal of the current study was to investigate the short-term test-retest reliability of event-related potential (ERP) and behavioral responses to novel stimuli in cognitively normal older adults. ERPs and viewing durations were recorded in 70 healthy older adults participating in a subject-controlled visual novelty oddball task during two sessions occurring seven weeks apart. Mean midline P3 amplitude and latency, mean midline amplitude during successive 50ms intervals, temporospatial factors derived from principal component analysis, and viewing duration in response to novel stimuli were measured during each session. ANOVAs revealed no reliable differences in the value of any measurements between time 1 and 2. Intraclass correlations (ICCs) between time 1 and 2 were excellent for mean P3 amplitude (ICC = .86), the temporospatial factors consistent with the P3 components (ICC of .88 and .76 respectively) and viewing duration of novel stimuli (ICC=.81). Reliability was only fair for P3 peak latency (ICC=.56). Successive 50ms mean amplitude measures from 100-1000ms yielded fair to excellent reliabilities, and all but one of the 12 temporospatial factors identified demonstrated ICCs in the good to excellent range. We conclude that older adults demonstrate substantial stability in ERP and behavioral responses to novel visual stimuli over a seven-week period. These results suggest that older adults may have a characteristic way of processing novelty that appears resistant to transient changes in their environment or internal states, which can be indexed during a single testing session. The establishment of reliable measures of novelty processing will allow investigators to determine whether proposed interventions have an impact on this important aspect of behavior.